High-temperature dislocation substructures in heavy-ion irradiated long-range-ordered (Fe, Ni)3V alloy - Hui Liu; Shiwei Wang; Xiaoou Yi; Wentuo Han; Hucheng Yu; Sichen Dong; Pingping Liu; Shulei Li; Somei Ohnuki; Farong Wan (Journal of Materials Research and Technology)
L12-type (Fe, Ni)3V alloy is a material system of rich potential for application in structural components for advanced nuclear reactor systems. This investigation probed into the displacement damage effects in long-range-ordered (Fe, Ni)3V and a control group of disordered Fe3V alloy, subjected to 6 MeV Fe4+ ion irradiation at 600 °C, up to a total fluence of 9.172 × 1018 ions·m−2 (peak damage: ∼0.9 dpa). The alloys demonstrated structural stability after irradiation, with a damage microstructure predominated by dislocations. Dislocation substructures in Fe3V consisted of loops, lines, and complex entanglements, whereas those in (Fe, Ni)3V displayed anomalies in both configuration and spatial distribution. They were observed in discrete bundles, interwoven with wavy line dislocations, and extended over 1 μm into the unirradiated regime. Dislocations in (Fe, Ni)3V featured a reduced size but a higher density after irradiation, compared to those in Fe3V. This difference may be attributed to the presence of anti-phase boundaries, which act as preferential sites for vacancy absorption, thereby increasing the survival rate of SIAs and interstitial-type defects. Dislocation bundles in (Fe, Ni)3V shared a common crystallographic geometry with the pre-existing planar slip bands. During irradiation, these slip bands may have attracted and assembled dislocation segments, leading to the formation of dislocation bundles. The slip bands may have also served as pathways for dislocation transport via radiation-enhanced glide, effectively expanding the spatial extent of the bundles. A greater sensitivity to irradiation hardening was found in L12-type (Fe, Ni)3V, primarily due to the development of dislocation bundles.